2001
DOI: 10.1093/carcin/22.12.2001
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effects of ONO-8711, a selective prostaglandin E receptor EP1 antagonist, on breast cancer development

Abstract: Levels of prostaglandin E(2) (PGE(2)) in human and rodent breast cancers are higher than surrounding normal tissues. PGE(2) exhibits biological activity through binding to membrane receptors, EP(1-4). The present study was designed to investigate the effects of ONO-8711, a newly synthesized selective PGE receptor EP(1) antagonist, on 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP)-induced breast cancer development. Starting at 7 weeks of age, female Sprague-Dawley (SD) rats were given PhIP (85 mg/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 22 publications
2
62
0
Order By: Relevance
“…To specifically determine whether the EP 1 receptor is functionally active in HCC cells, we used a selective EP 1 receptor agonist and antagonist to analyze their effects on cell viability and migration. Previous studies showed that the EP 1 receptor antagonist AH6809 inhibited anchorage-independent cell growth and reduced the viability of HCC cells [24] ; however, ONO-8711 significantly inhibited breast cancer and HCC development, presumably via induction of apoptosis [1,25] . Our data showed that the selective EP 1 receptor agonist ONO-DI-004 dramatically increased cell viability and migration in HCC cells in a dose-dependent manner and that the EP 1 receptor antagonist ONO-8711 exerted an inhibitory effect.…”
Section: Discussionmentioning
confidence: 97%
“…To specifically determine whether the EP 1 receptor is functionally active in HCC cells, we used a selective EP 1 receptor agonist and antagonist to analyze their effects on cell viability and migration. Previous studies showed that the EP 1 receptor antagonist AH6809 inhibited anchorage-independent cell growth and reduced the viability of HCC cells [24] ; however, ONO-8711 significantly inhibited breast cancer and HCC development, presumably via induction of apoptosis [1,25] . Our data showed that the selective EP 1 receptor agonist ONO-DI-004 dramatically increased cell viability and migration in HCC cells in a dose-dependent manner and that the EP 1 receptor antagonist ONO-8711 exerted an inhibitory effect.…”
Section: Discussionmentioning
confidence: 97%
“…PGE 2 elicits cellular responses via interaction with four cell surface receptors, EP [1][2][3][4] . Several studies suggest that the role of specific EP receptors varies in different tumor types (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…15 Recent data suggest that antagonists (ONO-8711), which specifically block EP 1 receptor, may also exhibit chemopreventive activity in several animal models of epithelial malignancy including breast cancer. 16,17 A study by Zhao et al 18 has also shown that the EP 1 and EP 2 receptors play an important role in the regulation of aromatase, which synthesises oestrogens locally in the breast.…”
mentioning
confidence: 99%
“…16 EP 1 expression in human breast has not been studied before. We studied the expression of human EP 1 receptors by immunohistochemistry in malignant breast lesions along with COX-2, oestrogen receptor (ER), progesterone receptor (PR) and HER-2/neu to correlate the pattern of expression with known prognostic factors in breast cancer.…”
mentioning
confidence: 99%